Assessing the Effectiveness of Corporate Legal Accountability in Ensuring Workers' Rights in Batam City - Agustin, Indri Ceria; Tan, David; Seroja, Triana Dewi (Universitas Muhammadiyah Sumatera Utara, 2025)
This study investigates the effectiveness of corporate legal accountability in upholding workers’ rights in Batam City, with specific reference to two case studies: PT. GSW (road construction sector) and PT. SRI (real estate sector). Employing an empirical legal research design with a qualitative approach, data were collected through questionnaires, document analysis, and in-depth interviews, grounded in the relevant labor law framework. The findings reveal that PT. SRI demonstrates stronger compliance with labor regulations through rigorous internal oversight and inclusive employment policies. Conversely, PT. GSW exhibits shortcomings in compensating contract workers, despite fulfilling social security obligations for permanent staff. Key determinants of corporate responsibility in protecting labor rights include the regulatory environment, employee performance, and labor market dynamics. Furthermore, external factors such as market competition, workforce heterogeneity, and inadequate government supervision exacerbate the challenges in labor rights enforcement. This research contributes to the understanding of corporate labor practices in Indonesia and offers policy-oriented recommendations, including enhanced labor law enforcement, improved worker education, stronger trade union advocacy, and tripartite collaboration among the government, employers, and employees to foster a fair and sustainable labor system.